Heart failure outcomes and empagliflozin effects in patients with heart failure and reduced ejection fraction in sinus rhythm or atrial fibrillation: Data from EMPEROR-Reduced - Böhm, Michael; Butler, Javed; Abdin, Amr; Filippatos, Gerasimos; Ferreira, João Pedro; Pocock, Stuart J.; Brückmann, Martina; Ofstad, Anne Pernille; Schueler, Elke; Wanner, Christoph; Zannad, Faiez; Anker, Stefan D.; et al. (European journal of heart failure, 2025)
Aims Empagliflozin reduces cardiovascular death (CVD) or hospitalization for heart failure (HHF), slows estimated glomerular filtration rate (eGFR) decline and improves quality of life (QoL) in heart failure with reduced ejection fraction (HFrEF). Whether the effect of empagliflozin is consistent according to atrial fibrillation (AF) status is worth exploring. Methods and results The impact of AF versus sinus rhythm (SR) on outcomes as well as on eGFR decline and QoL were studied post-hoc in EMPEROR-Reduced. Of patients with available rhythm analyses and after exclusion of patients with missing or paced rhythms, 2785 were included (AF, n = 928, SR, n = 1857). Differences were not significant for the primary endpoint (p = 0.66), first (p = 0.19) and recurrent HHF (p = 0.45). On placebo, alcohol consumption (interaction p = 0.32), body mass index (interaction p = 0.93), diabetes (interaction p = 0.52), hypertension (interaction p = 0.24) were not different between AF and SR. Low ejection fraction and high Kidney Disease: Improving Global Outcomes (KDIGO) class had higher event rates but without interaction between SR and AF, respectively. After a median follow-up of 20 months, empagliflozin reduced CVD or HHF compared to placebo in AF and SR (hazard ratio [HR] 0.82, 95% confidence interval [CI] 0.63-1.08; and HR 0.69, 95% CI 0.56-0.84; interaction p = 0.29). The same applied to time to first HHF (interaction p = 0.20), while there was a borderline but insignificant interaction for first and recurrent HHF (p = 0.10). The effect on annual eGFR decline and QoL scores was not different. Incident AF was numerically lower but formally not significantly different (HR 0.66, 95% CI 0.40-1.09, p = 0.11, empagliflozin vs. placebo). Conclusions In HFrEF, AF did not significantly modify outcomes after adjustment and did not associate with eGFR slopes. Empagliflozin reduced outcomes, eGFR decline and improved QoL regardless of AF or SR and probably reduced incident AF.
Erstmals veröffentlicht: 16. September 2025
Gesehen am 13.10.2025